2019
DOI: 10.21203/rs.2.17243/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of Causes of Death Among Brought-in-Dead Cases in a Third-Level Hospital in Lusaka, Republic of Zambia, Using the Tariff Method 2.0 for Verbal Autopsy: A Cross-Sectional Study

Abstract: Background Over one third of deaths in Zambian health facilities involve someone who has already died before arrival (i.e., brought in dead [BiD]), and in most BiD cases, the causes of death (CoD) have not been fully analyzed. Therefore, this study aimed to analyze the CoD of BiD cases using the Tariff Method 2.0 for automated verbal autopsy (VA), which is called SmartVA.Methods The target site was one third-level hospital in the Republic of Zambia’s capital city. All BiD cases aged 13 years and older at thi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…7 In a growing number of cases, when a death occurs, the deceased is taken to a health facility by the relatives to obtain a death notification form required for death registration and burial permission from the civil registration office. 8 Investigations revealed that more than one third of deaths recorded at health facilities were those that occurred before their arrival (ie, brought-in-dead cases). Facility health information officers reported that the CoD of brought-indead cases was difficult to ascertain because of little medical information available regarding what led to death.…”
Section: Challenges In Ascertaining Cod Of Cases That Occurred In Communities In Zambiamentioning
confidence: 99%
See 1 more Smart Citation
“…7 In a growing number of cases, when a death occurs, the deceased is taken to a health facility by the relatives to obtain a death notification form required for death registration and burial permission from the civil registration office. 8 Investigations revealed that more than one third of deaths recorded at health facilities were those that occurred before their arrival (ie, brought-in-dead cases). Facility health information officers reported that the CoD of brought-indead cases was difficult to ascertain because of little medical information available regarding what led to death.…”
Section: Challenges In Ascertaining Cod Of Cases That Occurred In Communities In Zambiamentioning
confidence: 99%
“…The details of this study have been described elsewhere. 8 In brief, for 1,571 brought-in-dead cases more than 1 month old, trained staff interviewed the deceased's relatives and CoD was derived using SmartVA, an automated verbal autopsy computer program validated in previous studies and recommended by the WHO. [9][10][11] The CoD written in the officially issued death notification form was also retrieved for each case.…”
Section: Challenges In Ascertaining Cod Of Cases That Occurred In Communities In Zambiamentioning
confidence: 99%